STUDI KINERJA PT BNI SYARIAH SESUDAH PEMISAHAN (SPIN OFF) DARI PT BANK BNI (PERSERO) TBK - Achmad Chotib; Wiwik Utami (Akuntabilitas, 2014)
The purpose of this study was to analyze the performance of BNI Syariah beforethe spin-off compared with after the spin-off and to analyze the performance of BNI Syariahafter the spin-off compared with the performance of BJB Syariah after the spin off. Both of theperformance analysis based on CAR, NPF, NPM, ROA, ROE, and FDR. The study wasconducted by using analysis Paired Sample T-Test and analysis Independent Sample T-Test.The results showed that the performance of BNI Syariah before and after the spin-off does notdifference significantly. Likewise for the comparation of BNI Syariah and BJB Syariah afterspin off, some ratios (NPF, NPM, ROA, ROE) did not differ significantly with probabilitygreater than 0.05, and for CAR and FDR, there was a significant difference with probabilitylower than 5 percentDOI: 10.15408/akt.v7i2.2661